Mampukah Progressive Muscle Relaxation (PMR) Menurunkan Kadar Gula Darah? - casman, casman (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2019)
Background: People with diabetes mellitus increase every year, diabetes mellitus is a disease characterized by hyperglycemia, which is high blood sugar levels. People with diabetes mellitus usually get the stress throughout their lives. Some prevention can be usefull on patients to prevent complications, progressive muscle relaxation can increase insulin absorption and reduce stress.Objective: to examine the effectiveness of progressive muscle relaxation in reducing fasting blood sugar levels. Method: This article is part of a previous study, with tittle differences in the effectiveness of progressive muscle relaxation and physical exercise in reducing blood sugar levels in people with diabetes mellitus type 2. Progressive muscle relaxation is carried out for 6 consecutive days, two sessions per day, with duration 30 minutes per session. Results: on average the respondents were 50.37 years old, and the results showed that p = 0,000 (p <0.05), ie there was a decrease in fasting blood sugar levels in the intervention group from 171.93 mg / dL (pre) to 121, 73 mg / dL (post).Conclusion: progressive muscle relaxation with minumum duration 30 minutes is effective in reducing fasting blood sugar levels in elderly with diabetes mellitus type 2.